The Moderating Role of Industry Type on the Effect of Sustainability Report Disclosure on Firm Value: Evidence from Indonesia - Desi Yuniasih; Dewi Darmastuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
This study aims to find empirical evidence of the role of industry type in moderating the effect ofthe sustainability report disclosure on firm value. This study uses panel data regression analysisof 41 non-financial sector companies listed on the Indonesia Stock Exchange (IDX) andconsistently published annual and sustainability reports from 2018 to 2020. the findings showthat sustainability report disclosure, economic disclosure, and environmental disclosure do notsignificantly affect firm value. In contrast, social disclosure has a significant positive effect on firmvalue. In the other case, industry type only strengthens the effect of economic, environmental,and social disclosure on firm value. Overall, it shows that management thinks investing in environmental or publishing sustainability reports could bring some economic issues, which will lover the market value. High-profile companies tend to be more concerned about disclosing their sustainability performance because they have more responsibility for their business process. This study provides insight into the effect of industry type in moderating the relationship between sustainability report disclosure and firm value, which has not been widely studied, especially in Indonesia. Regulators can consider the results of this study regarding the sustainability reports disclosure.